Development Of Computer-Assisted Chemistry Learning Media With The Macromedia Flash Program To Measure Problem-Solving Abilities - Afni, Khairul; Silaban, Ramlan (Yana Research, 2023)
Efforts to improve the quality of education are influenced by the factors involved during the learning process; such as teachers, curriculum, infrastructure, and the environment. This is in line with Law no. 20 of 2003 which states that